Qualidade e potencial funcional da porção comestível e do óleo de frutos de palmeiras nativas oriundas do Amapá - Santos, Mary de Fátima Guedes dos (2012)
Native palm trees belong to Arecaceae family and are among the most useful plant resources for the Amazon man. Despite the great diversity and utilities, few species can be considered economically important, being necessary to perform more comprehensive studies on quality for species not yet explored. This study aimed to evaluate the quality, bioactive compounds and functional potential of native fruit and palm oils derived from Amapá. We evaluated bacaba, buriti inajá, pupunha and tucumã fruits and oils. Initially, there was characterized both physical and physicochemical of fruit, then evaluated bioactive compounds and total antioxidant activity by ORAC methods, DPPH and β-carotene / linoleic acid. Subsequently, the oils were extracted by Soxhlet and held a full characterization of their major and minor components by gas chromatography and high performance liquid chromatography, were also evaluated their physicochemical characteristics, oxidative stability in Rancimat equipment, unsaponifiable matter and polar compounds. Among the physical characteristics of the fruits, the pupunha palm stands out for its high yield (76,38 %). In physicochemical tests, were observed, among others, high levels of starch in pupunha and inajá (24,89 and 14,49 %, respectively) and total pectin (overall mean 0,81 %). The fruits of palm trees stood out by the high content of PET, especially bacaba and tucumã (941,56 and 158,98 mg of galic acid.100g-1, respectively), total carotenoids in tucumã and buriti (7,24 and 4,67 mg 100g-1, respectively) and anthocyanins in bacaba (80,76 mg 100g-1). As for the antioxidant capacity, bacaba had the highest total antioxidant activity by ORAC method (194,67 μM Trolox.g-1), DPPH (47,46 g-1 pulp.g DPPH) and β-carotene / linoleic acid (92,17 % I.O). Bacaba, inajá, buriti, tucumã and pupunha oils, presented percentages of fatty matter about 38, 35, 28, 26 and 17 %, respectively. Buriti, bacaba and tucumã oils presented a high content of unsaturated fatty acids with more than 73, 70 and 67 %, respectively, for triglycerides, in general, there is a predominance of species with 50, 52 and 54 carbon atoms identified as (POP, POO and OOO). In referring to the minor compounds, sterols are present in significant amounts in all samples, particularly in pupunha and tucumã oils (4456 and 2708 mg.kg-1), the tocopherols have been found in larger quantities in buriti and tucumã oils (1567 and 483 mg.kg-1), for the carotenoids, the β-carotene group showed 90% higher concentrations of oil, and the tucumã has the highest concentrations (1222,33 mg.kg-1) followed by buriti, pupunha and inajá. By physicochemical characteristics obtained, as low levels of acidity (<2,4 %) and peroxide (<12,0 meq O2.kg-1), unsaponifiable matter values below 2,0 %, great stability toward oxidation and polar compounds between 3,3 and 5,2 %, oils studied here showed little change. Both fruits and oils exhibited excellent quality characteristics, as well as proved nutritional potential.